Testing Dyadic Coping, Marital Adjustment and Anxiety as moderators of Fathers Pre-Natal Attachment - Brites, Rute (2018)
Despite extensive evidence on the influence of couples’ relationship variables on motherinfant attachment, few studies have addressed father’s perspective. This study investigates the impact of dyadic coping, marital adjustment (consensus) and anxiety on fathers’ prenatal attachment. A community sample of 250 men, aged 21-52 years old (M = 32.95; SD = 5.94), completed DAS-Dyadic Adjustment Scale (Spanier, 1976), DCI-Dyadic Coping Inventory (Bodenmann, 2008), HADS-Hospital Anxiety and Depression Scale (Zigmond, & Snaith, 1983) and PAASPaternal Antenatal Attachment Scale (Condon, 1993). All men were in a stable relationship with the mother to be. Most were first time fathers (n = 128, 55.2%), with a high school or a university degree (n = 145, 59%). Following missing data analysis the SEM was evaluated in two steps with AMOS software: a) quality of measures adjustment b) causal model. The global measure model presented a good fit (CFI = .89; GFI= .70; RMSEA = .07; P[rmsea ≤ .05 < .001; MECVI = 4.51). The path analysis DCI > Attachment is a stronger one (B DCI,PAAS = 0.27; SE = .11; β DCI,PAAS = .17; p = .01). Although the other paths have a lower impact on attachment, together they improve the model explaining fathers’ pre-natal attachment, and producing an overall better fit. Results highlight the importance of further studies addressing the transition to parenthood from the perspective of fathers to be. In future models, individual as well as other couples’ relationship variables should be considered.